Reversible Bilateral Basal Ganglia and Brainstem Lesions in Neuropsychiatric Systemic Lupus Erythematosus: A Case Report - Rocksy Fransisca V. Situmeang; Reza Stevano; Ekawaty Yasinta Yohana Larope; Ratna Sutanto (Medicinus, 2022)
The pathophysiology behind neuropsychiatric SLE (NPSLE) remains poorly understood and its clinical and radiological manifestations are highly varied. In this report, we present a complex case of an adolescent female patient with a three-week history of systemic symptoms (fever, nausea, vomiting, weight loss, polyarticular joint pain), progressive motor weakness, tremor, and altered mental status. Physical examination was significant for oromandibular and cervical dystonia rigidity, and general weakness with imposed right-sided hemiparesis. A head MRI demonstrated bilateral hyperintense lesions of the basal ganglia and brainstem, without restricted diffusion. The patient was diagnosed with NPSLE, lupus nephritis, electrolyte imbalance, severe hypoalbuminemia, lupus cardiomyopathy, autoimmune hemolytic anemia, pulmonary tuberculosis, and sepsis. The patient was given treatment in the ICU with pulse dose corticosteroids, intravenous antibiotics, intravenous immunoglobulins (IVIg), and supportive treatment with correction of hematologic and electrolyte abnormalities. Her condition improved rapidly. Full alertness was regained, and symptoms of oromandibular dystonia, tremor, and weakness diminished significantly. A follow-up MRI three weeks later revealed the complete disappearance of lesions, which we attribute to the resolution of the inflammatory process in the brain.